The Origin of the Universe as Revealed Through the Polarization of the Cosmic Microwave Background - Dodelson, S; Easther, R; Hanany, S; McAllister, L; Meyer, S; Page, L; Ade, P; Amblard, A; Ashoorioon, A; Baccigalupi, C; Balbi, A; Bartlett, J; et al. (2009)
Modern cosmology has sharpened questions posed for millennia about the origin of our cosmic habitat. The age-old questions have been transformed into two pressing issues primed for attack in the coming decade: How did the Universe begin? and What physical laws govern the Universe at the highest energies? The clearest window onto these questions is the pattern of polarization in the Cosmic Microwave Background (CMB), which is uniquely sensitive to primordial gravity waves. A detection of the special pattern produced by gravity waves would be not only an unprecedented discovery, but also a direct probe of physics at the earliest observable instants of our Universe. Experiments which map CMB polarization over the coming decade will lead us on our first steps towards answering these age-old questions.